Saving social security - Edward Lane (Levy Economics Institute of Bard College, 2024)
For more than 25 years, the Social Security Trust Fund has been projected to run out of money in 2033 (give or take a few years), potentially causing benefits to be severely reduced in the absence of corrective legislative action. Today (February 2024), projections are made by the Social Security Administration that indicate that future benefits will need to be reduced by roughly 25 percent or taxes will need to be increased by about 33 percent, or some combination to avoid benefit curtailment. While Congress will most probably prevent benefits from being reduced for retirees and those nearing retirement, the longer Congress and the president take to address the shortfall, the more politically unpalatable (and possibly draconian) the solutions will be for all others. Dozens of proposals are being evaluated to address the long-term problem by mainstream benefits experts, economists, think tanks, politicians, and government agencies but, with rare exceptions from a few economists, none address the short-term problem of Trust Fund depletion, provide a workable roadmap for the long-term challenges, or consider fundamental financing differences between the federal government and the private sector. This paper aims to address these issues by suggesting legislative changes that will protect the Social Security system indefinitely, help ensure the adequacy of benefits for retirees and their survivors and dependents, and remove confusing and misleading legislative and administrative complexity. In making recommendations, this paper will demonstrate that the Social Security Trust Funds, while legally distinct, are essentially an artificial accounting contrivance within the US Treasury that have become a tool to force program changes that, for ideological reasons, will likely shift an increasing financial burden onto those who can least bear it. Finally, while the focus of this paper is on the Social Security system, it would be incomplete without also addressing, albeit in a limited way, the larger political issue of the nation's debt and deficit along with the implications for inflation.
Keywords: H00; H50; H51; H53; H55; H61; H62; H63; H64; H21; H22; H23; H24; H31; E62; 330; Social Security; FICA; Taxation; Taxes; Trust Fund; Trust Funds; OASI; OASDI; Medicare; Deficit; Inflation; Welfare; Treasury; Debt; Old-age